Basic Mechanism of Surface Topography Evolution in Electron Beam Based Additive Manufacturing - Breuning, Christoph; Pistor, Julian; Markl, Matthias; Körner, Carolin (Materials, 2022)
This study introduces and verifies a basic mechanism of surface topography evolution in electron beam additive manufacturing (E-PBF). A semi-analytical heat conduction model is used to examine the spatio-temporal evolution of the meltpool and segment the build surface according to the emerging persistent meltpool domains. Each persistent domain is directly compared with the corresponding melt surface, and exhibits a characteristic surface morphology and topography. The proposed underlying mechanism of topography evolution is based on different forms of material transport in each distinct persistent domain, driven by evaporation and thermocapillary convection along the temperature gradient of the emerging meltpool. This effect is shown to be responsible for the upper bound of the standard process window in E-PBF, where surface bulges form. Based on this mechanism, process strategies to prevent the formation of surface bulges for complex geometries are proposed.
CRIS-Team Scopus Importer:2022-07-22
Keywords: additive manufacturing; electron beam; heat transfer; process modeling; processing window; topography